Food expenditure shares and income elasticities in Zimbabwe: Accounting for gender and poverty differences - Conrad Murendo; Grown Chirongwe; Givious Sisito (Cogent Economics & Finance, 2022)
This study analysed food expenditure patterns and income elasticities differentiated by gender of household head and income levels. Data came from 32, 256 households drawn from the Zimbabwe Poverty, Income, Consumption and Expenditure Survey of 2017. Female headed households had higher vegetable and fruit expenditures while male headed households had higher expenditure shares on animal protein sources. Poorer households had poor dietary choices characterized by higher consumption of starchy foods and lower consumption of fruits, eggs, and milk. All income elasticities of all food items and groups were positive, indicating they were normal goods and increasing income will contribute to more diversified diets. Richer groups spend a lower share of their income on food compared to their poorer counterparts. The income elasticities for vegetables, bread, maize, and poultry were high for the poorest households, implying an increase in income would substantially increase their consumption. Policies aimed at increasing household income are vital to improve food consumption. Poor households and male headed households allocated higher proportion of income to food budget than the non-poor and female headed households. Food aid and social protection schemes, for example, income transfers should target very poor households to help them get access to better diets and cushion them from food price increase. Food consumption patterns and income elasticities varied by gender of household head and income group. Therefore, targeted food policies should be formulated based on specific food demand patterns for each group of households.
Keywords: 330; expenditure patterns; income elasticity; socio-economic groups; food policy; Zimbabwe